2016
DOI: 10.1158/0008-5472.can-15-1144
|View full text |Cite
|
Sign up to set email alerts
|

YAP Mediates Tumorigenesis in Neurofibromatosis Type 2 by Promoting Cell Survival and Proliferation through a COX-2–EGFR Signaling Axis

Abstract: The Hippo-YAP pathway has emerged as a major driver of tumorigenesis in many human cancers. YAP is a transcriptional coactivator and while details of YAP regulation are quickly emerging, it remains unknown what downstream targets are critical for the oncogenic functions of YAP. To determine the mechanisms involved and to identify diseaserelevant targets, we examined the role of YAP in neurofibromatosis type 2 (NF2) using cell and animal models. We found that YAP function is required for NF2-null Schwann cell s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 51 publications
0
57
0
Order By: Relevance
“…Hippo signaling pathway maintained tissue growth balance by cell proliferation inhibition and promoting apoptosis. [42][43][44] Dysregulation of Hippo signaling were identified during malignancy formation, 32,45 including HCC. 33 YAP is a crucial effector in Hippo signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Hippo signaling pathway maintained tissue growth balance by cell proliferation inhibition and promoting apoptosis. [42][43][44] Dysregulation of Hippo signaling were identified during malignancy formation, 32,45 including HCC. 33 YAP is a crucial effector in Hippo signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Nf2 deletion in the murine liver leads to the expansion of Sox9 + CK19 + liver progenitor cells (LPCs) and development of cholangiocarcinoma (CC) as well as hepatocellular carcinoma (HCC) in a Yap-dependent manner (Liu-Chittenden et al, 2012; Yimlamai et al, 2014; Zhang et al, 2010). The importance of Yap as a downstream effector of Merlin has been subsequently confirmed in NF2-relevant cell types (Guerrant et al, 2016; Lavado et al, 2013; Serinagaoglu et al, 2015), underscoring the value of the liver model in elucidating the molecular mechanisms of Nf2 tumorigenesis.…”
Section: Introductionmentioning
confidence: 91%
“…The mammalian Hippo pathway has been a source of great interest in the development of NF2-deficient schwannomas. Guerrant and colleagues recently found that COX-2 is transcriptionally up regulated by YAP, a Hippo pathway effector that is transcriptionally activated in the setting of NF2- deficiency [ 6 ]. Further, that same group demonstrated that the COX-2 inhibitor celecoxib suppressed tumor expansion in an orthotopic model of tumorigenesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%